Developing a Core Outcome Set for blood purification in hypertriglyceridemic acute pancreatitis: a Delphi study protocol - Guo, Shengteng; Zhu, Haoran; Zhao, Rongzhen; Guan, Qinghai; Wu, Juan; Wang, Qinghua (Frontiers in Medicine, 2025)
BackgroundEarly initiation of lipid-lowering therapy is crucial for controlling disease progression and preventing recurrent acute pancreatitis in patients with hypertriglyceridemic acute pancreatitis (HTGP). As a clinically common intervention for HTGP, blood purification enables rapid clearance of serum triglycerides. However, the current absence of a standardized outcome measurement system for blood purification in HTGP hinders systematic therapeutic evaluation by clinicians and further impedes the integration and comparison of research findings. Consequently, this study aims to develop a Core Outcome Set (COS) for blood purification in HTGP, standardizing the assessment of treatment efficacy and enhancing comparability across similar studies.MethodsThe COS will be developed in accordance with the Core Outcome Measures in Effectiveness Trials (COMET) Handbook, Core Outcome Set-STAndardised Protocol (COS-STAP), Core Outcome Set-STAndards for Development (COS-STAD), and Core Outcome Set-STAndards for Reporting (COS-STAR). First, research team members and a stakeholder panel will be recruited. Outcome indicators relevant to stakeholders will be identified through systematic reviews and interviews. The stakeholder panel and domain experts will then participate in a two-round Policy Delphi process followed by a consensus meeting to discuss and score potential outcomes, ultimately determining the final COS. The finalized COS will be disseminated via a peer-reviewed publication and a checklist to facilitate implementation and promotion.DiscussionThe COS for blood purification in HTGP will establish a standardized, evidence-based outcome measurement framework. This structured approach will: (1) Enable comprehensive therapeutic evaluation by clinical teams, (2) Enhance precision in disease progression control, (3) Reduce heterogeneity across comparable studies, and may ultimately inform global treatment practices for HTGP.Standardized registration statementThis study has been prospectively registered with the Core Outcome Measures in Effectiveness Trials (COMET) initiative (ID: 3231; Accessible at: https://www.comet-initiative.org/Studies/Details/3231) and the China Clinical Trial Core Outcome Sets Research Center (ChiCOS) (ID: CHICOS2024000024; Accessible at: https://www.chicos.org.cn/home).